The Role of Family Social Support in Restoring Social Functioning among Child Victims in Conflict with the Law - Abelia Riski Alifta; Permata Jali Dimasiosz; Alfian Mahendra; Iqbal Rahmat Gani; Muhammad Anggi Pratama (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2026)
Children in conflict with the law as victims are vulnerable to psychosocial problems, including fear, shame, social withdrawal, and low self-confidence, which may impair their social functioning. This study examines forms of family social support and their contribution to restoring the social functioning of child victims in Bengkulu City, Indonesia. A descriptive qualitative approach was employed using observation, in-depth interviews, and documentation. Nine informants participated, comprising three child victims, four family members, one social worker, and one psychologist. Data were analyzed through open coding, categorization, source triangulation, and thematic interpretation based on the social support dimensions of Sarafino and Smith and the social functioning indicators of the Indonesian Ministry of Social Affairs. Findings indicate that emotional support fostered feelings of safety and confidence, informational support enhanced understanding of legal processes, instrumental support facilitated access to daily needs and services, and appraisal support strengthened self-acceptance. Comprehensive family support was associated with gradual restoration of social functioning, whereas inconsistent support hindered recovery. The study contributes by identifying how specific dimensions of family social support promote family-based rehabilitation and social reintegration of child victims in Indonesia.